2000
DOI: 10.1017/s0033291799002019
|View full text |Cite
|
Sign up to set email alerts
|

Life events and prodromal symptoms in bulimia nervosa

Abstract: The prodromal phase of bulimia nervosa was found to be characterized by a combination of prodromal symptoms of affective type and stressful life events. Their joint occurrence may increase vulnerability to bulimia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
1
39
0
1
Order By: Relevance
“…The experience of irritability is unpleasant and elicits stress-related physiological responses [34]. Irritable mood has been described to be one of the prodromal symptoms of bulimia nervosa [35]and may also persist as a residual feature after the treatment of actual bulimic symptoms. In clinical practice, generalised irritable mood should be considered when adolescents present with dyscontrol behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of irritability is unpleasant and elicits stress-related physiological responses [34]. Irritable mood has been described to be one of the prodromal symptoms of bulimia nervosa [35]and may also persist as a residual feature after the treatment of actual bulimic symptoms. In clinical practice, generalised irritable mood should be considered when adolescents present with dyscontrol behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Management of irritability may be preventive of psychosomatic disorders such as bulimia. Further, in the treatment of bulimia nervosa, management of residual irritable moods may be advisable for a more lasting treatment outcome [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The scale ranges from ‘changes due to environment absent or very rare’ (score 1) via ‘nonspecific factors, such as having someone to talk to, produce limited improvement’ (score 3) to ‘the source of the depression is entirely dependent on certain specific situations, being regularly precipitated or entirely removed according to them’ (score 7). This item was found to sensitively discriminate between different subgroups of depressed patients [26,27,28,29], to be exceedingly common in patients with neurocirculatory asthenia [30] and also in the prodromal phase of bulimia nervosa compared to control subjects [31]. It was thus expected to yield a sensitive measurement of change upon treatment in cyclothymic disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Subclinical mood disturbances were found to be exceedingly common in the prodromal phase of bulimia nervosa [122,123]. The interview discriminated sensitively between patients and controls on anorexia/strict diet, on ratings of low self-esteem, depressed mood, generalized anxiety, reactivity to social environment, phobic avoidance, irritability, and guilt.…”
Section: Resultsmentioning
confidence: 99%
“…Raffi et al [122,123] found that, in normal subjects, the CID total score was significantly negatively correlated with two dimensions (environmental mastery and positive relations with others) of Ryff’s Psychological Well-Being scales, while no significant correlations were found among remitted patients. In another study [133], persistent residual symptoms, as measured by the modified version of the CID, in remitted patients with panic disorder and agoraphobia were found to be correlated negatively and significantly with well-being subscales, and these correlations were similar also in control subjects.…”
Section: Resultsmentioning
confidence: 99%